2016
DOI: 10.1103/physreve.93.052215
|View full text |Cite
|
Sign up to set email alerts
|

Exposing local symmetries in distorted driven lattices via time-averaged invariants

Abstract: Time-averaged two-point currents are derived and shown to be spatially invariant within domains of local translation or inversion symmetry for arbitrary time-periodic quantum systems in one dimension. These currents are shown to provide a valuable tool for detecting deformations of a spatial symmetry in static and driven lattices. In the static case the invariance of the two-point currents is related to the presence of time-reversal invariance and/or probability current conservation. The obtained insights into… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 37 publications
0
26
0
Order By: Relevance
“…quantum systems with local symmetries. It is only recently that it has been shown [11][12][13][14][15][16][17][18][19][20] that the unique feature of the presence of local symmetries are the existence of invariant two-point correlator currents. However, all of these works address the case of one-dimensional stationary and non-interacting wave mechanical setups ranging from acoustics, optics to quantum mechanics and make no statement how a more general concept of local symmetries could look like, in particular in the case of dynamically interacting quantum systems.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…quantum systems with local symmetries. It is only recently that it has been shown [11][12][13][14][15][16][17][18][19][20] that the unique feature of the presence of local symmetries are the existence of invariant two-point correlator currents. However, all of these works address the case of one-dimensional stationary and non-interacting wave mechanical setups ranging from acoustics, optics to quantum mechanics and make no statement how a more general concept of local symmetries could look like, in particular in the case of dynamically interacting quantum systems.…”
Section: Discussionmentioning
confidence: 99%
“…The ITPC are the key quantities characterizing local discrete symmetries in one spatial dimension as has been shown in several works [13][14][15][16][17][18][19][20]. Applications to photonic multilayers have demonstrated that perfectly transmitting resonances can be completely classified according to sum rules imposed on the ITPC [14].…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations